Impact of GAP-43, Cx43 and actin expression on the outcome and overall survival in diffuse and anaplastic gliomas - Krigers, Aleksandrs; Demetz, Matthias; Moser, Patrizia; Kerschbaumer, Johannes; Brawanski, Konstantin R.; Fritsch, Helga; Thomé, Claudius; Freyschlag, Christian F. (Scientific reports, 2023)
Distant intercellular communication in gliomas is based on the expansion of tumor microtubuli, where actin forms cytoskeleton and GAP-43 mediates the axonal conus growth. We aimed to investigate the impact of GAP-43 and actin expression on overall survival (OS) as well as crucial prognostic factors. FFPE tissue of adult patients with diffuse and anaplastic gliomas, who underwent first surgery in our center between 2010 and 2019, were selected. GAP-43, Cx43 and actin expression was analyzed using immunohistochemistry and semi-quantitatively ranked. 118 patients with a median age of 46 years (IqR: 35–57) were evaluated. 48 (41%) presented with a diffuse glioma and 70 (59%) revealed anaplasia. Tumors with higher expression of GAP-43 ( p = 0.024, HR = 1.71/rank) and actin ( p < 0.001, HR = 2.28/rank) showed significantly reduced OS. IDH1 wildtype glioma demonstrated significantly more expression of all proteins: GAP-43 ( p = 0.009), Cx43 ( p = 0.003) and actin ( p < 0.001). The same was confirmed for anaplasia (GAP-43 p = 0.028, actin p = 0.029), higher proliferation rate (GAP-43 p = 0.016, actin p = 0.038), contrast-enhancement in MRI (GAP-43 p = 0.023, actin p = 0.037) and age (GAP-43 p = 0.004, actin p < 0.001; Cx43 n.s. in all groups). The intercellular distant communication network in diffuse and anaplastic gliomas formed by actin and GAP-43 is associated with a negative impact on overall survival and with unfavorable prognostic features. Cx43 did not show relevant impact on OS.